The Relevance of Financial Literacy to Indonesian Millennials' Behavior, Awareness, and Financial Independence - Ade Maharini Adiandari; Ayu Okvitawanli (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
This study aimed to understand various scientific study and scientific sources, namely, to find the relevance between Indonesian millennial financial literacy education and awareness of financial behavior to the financial independence of Indonesian millennial. To facilitate the discussion and explanation of this issue, we have carried out a series of literature data searches from various studies of journal publications, books, and academic procedures that discuss financial literacy issues and millennial behavior regarding finance. After getting the data, we analyzed it by providing consistent coding of the data, evaluating the data into several components, and summarize the implications of the findings so that we could produce a valid conclusion from various data points. Based on the discussion and analysis of the data, we can say that Indonesian millennial financial literacy is very relevant to financial behavior and in supporting the ability and thus capacity in reaching financial independence. We hope the results of this study become an essential input in future study efforts regarding financial behavior, especially of Indonesian millennial generation.